Family Sense of Coherence and Family and Partner Affective Attachment in Adolescents - Minić, Jelena Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In accordance with the basic principles of Antonovsky’s salutogenic model of health, this research examines the connection between the family sense of coherence as a central source of health and family and partner affective attachment, as a generalized sources of health. The aim of the research was to examine the relationship between family sense of coherence in adolescents with: family dimensions (avoidance and anxiety) and partner affective attachment models (model of the self and model of others). The research tasks were: to determine the differences in the intensity of the family sense of coherence relating to family and partner attachment styles (secure, avoidant, preoccupied and fearful); to determine differences in family dimensions (avoidance and anxiety) and partner affective attachment models (model of the self and model of others) relating to gender, age and place of residence of adolescents; to determine the intensity of family sense of coherence and distribution of family and partner attachment styles in adolescents. The study sample consisted of adolescents of both genders (n = 360, 15 to 24 years old, AS = 19.36; SD = 2.55) from Kosovo and Metohija and central Serbia. The survey used the following instruments: Scale for assessing family sense of coherence, Questionnaire for assessment of family affective attachment, Questionnaire for assessing partner affective attachments and Basic socio-demographic questionnaire. Descriptive statistics, Pearson’s correlation coefficient, T-test and Analysis of variance were used for data processing. The results of the research showed that adolescents with a secure family affective attachment style (low in anxiety and low in avoidance) and secure partner affective attachment model (positive model of the self and a positive model of others) have a stronger sense of family coherence. When it comes to differences in the intensity of the sense of family coherence in adolescents in relation to affective attachment styles, the survey results indicate that there are statistically significant differences in the intensity of the sense of family coherence in adolescents depending on the dominant family affective attachment style, but no difference when it comes to partner affective attachment. The results showed that the sense of family coherence is stronger in adolescents with secure family affective attachment style, compared with adolescents with avoidant and fearful family affective attachment style. It was found that the family sense of coherence is stronger in adolescents with preoccupied family affective attachment style, compared with adolescents with avoidant family affective attachment style. The research also determined differences in dimensions and models of affective attachment in relation to gender, age and place of residence. The obtained results show that: the male adolescents have more prominent avoidance (family attachment dimension) compared with the female adolescents; older adolescents (19 to 24 years old) have higher scores on the partner attachment models (on model of the self and others) compared with younger adolescents (15 to 19 years old); anxiety (family attachment dimension) is more prominent in younger adolescents and in adolescents from Kosovo and Metohija, compared with those from central Serbia. The results suggest that adolescents have adequate sources of health (they have a stronger sense of family coherence and predominance of the secure family and partner affective attachment style). The results confirm the hypothesis and are consistent with the results of some previous studies.